A formação do professor universitário no campo da saúde : a prática docente do enfermeiro - Silva, Karla Caroline Araújo (2021)
This research is linked to the Education of Teachers and Public Education Policies of the Public Educational Policies of the Postgraduate Program in Education at the Federal University of Mato Grosso of Mato Grosso (UFMT). Nurses and professor of nursing urdergraduate courses were investigated about their pedagogical practice. The problematic for this investigation is the one that has always permeated my entire experience as a teacher, which is the lack of pedagogical training of teaching professionals in the health sphere. Therefore, the general objective was stipulated: to analyze the pedagogical formation of nurses who work in Higher Education teaching in Rondonópolis (MT); and to complement the information, I highlight the specific objectives that were set: the pedagogical practice of the participants; the realization or not of continued and permanent education; to know the pedagogical project of the courses where they work, and to analyze the resources and elements used by them for their pedagogical work. Twelve teachers from nursing courses at UFMT and one private institution participated in this research. Data collection was performed through online semi-structured interviews using Google Meet and Skype tools, after the participants signed the Free Consent Form. Subsequently, the interviews were transcribed and submitted to content analysis, which were organized into axes for better analysis. So, discussing this theme resulted in an evaluation of several aspects, such as pedagogical, structural, political, and social aspects, which was effective in the results and confirmed several theories about teaching in higher education in the health field. Then, in this research it became clear how challenging the beginning of the teaching career is for professional nurses, who depend on constant experiences to build their identity as a teacher, facing daily obstacles, but which bring with them the resistance of the health professional to persist and propose ways of facing the several changes in the university context of our country. However, it is possible to notice experienced professionals who still face the devaluation of salaries, the lack of institutional support to execute their pedagogical practice, as well as the adversities and social conditions that health courses and health care assistance face, but who still play their role in an emancipating education where the student is the protagonist. I affirm that the beginning of the pedagogical change in the health area courses occurs from the moment that the teachers are able to visualize the importance of education for a society and understand the true role of mediator that they have, and then we will be able to believe in a fair, citizen and emancipating education.